Thought for Food: Understanding Educational Disparities in Food Consumption - Hale Koç; Hans van Kippersluis (Tinbergen Institute, 2015)
Higher educated individuals are healthier and live longer than their lower educated peers. One reason is that lower educated individuals engage more in unhealthy behaviours including consumption of a poor diet, but it is not clear why they do so. In this paper we develop an economic theory of unhealthy food choice, and use a Discrete Choice Experiment to discriminate between the theoretical parameters. Differences in health knowledge appear to be responsible for the greatest part of the education disparity in diet. However, when faced with the most explicit health information regarding diet, lower educated individuals still state choices that imply a lower concern for negative health consequences. This is consistent with a theoretical prediction that part of the education differences across health behaviours is driven by the "marginal value of health" rising with education.
Keywords: C25; I12; I24; 330; Health; Education; Diet; Discrete Choice Experiment